Effects of fumonisin B1 and mycotoxin binders on growth performance, tibia characteristics, gut physiology, and stress indicators in broiler chickens raised in different stocking densities. (20th December 2017) - Lee, S; Kim, D-H; Keum, M-C; Han, E; An, B-K; Chang, H-H; Choi, Y-H; Moon, B-H; Lee, K-W
Abstract: The present study was carried out to investigate the effects of stocking density, fumonisin B1 (FB), and mycotoxin binder (TB) on growth performance, bone quality, physiological stress indicators, and gut health in broiler chickens. Day-old Ross 308 male broiler chicks (n = 1, 440/experiment) were randomly allocated to 72 floor pens in a 3 × 2 × 2 factorial arrangement, using 3 stocking densities (12.5 birds/m 2 [HSD], 10 birds/m 2 [MSD], or 7.5 birds/m 2 [LSD]), 2 levels of purified FB (0 or 10 ppm), and 2 levels of TB (0 or 0.2%). Each treatment had 6 replicates (n = 6/treatment) and experiments lasted 34 days. All data were analyzed using 3-way ANOVA with stocking density level, FB, and TB as main factors. Body weight gain and feed intake were lower ( P < 0.05) in broilers kept at HSD and MSD compared to LSD-housed counterparts. Birds fed an FB-contaminated diet exhibited a higher feed-to-gain ratio compared with those fed an FB-free diet ( P < 0.05). None of the treatments affected intestinal morphology or ileal secretory immunoglobulin A levels. Stocking density affected tibia breaking strength ( P < 0.05), which was lower in chickens housed at HSD compared with LSD-housed chickens. The heterophil/lymphocyte ratio (H/L ratio) was elevated ( P < 0.05) in HSD and MSD groups compared with the LSD group. Serum nitric oxide (NO) levels were elevated ( P < 0.05) in chickens fed the FB-contaminated diet compared with the control diet-fed counterparts. Significant interaction ( P < 0.05) between FB and TB on serum NO levels was noted. In summary, increasing stocking density lowered growth performance and bone quality, but increased the H/L ratio. Dietary TB did not affect FB-induced increases in the feed-to-gain ratio. No interaction was observed between stocking density and FB for the measured variables.